Visual Metaphor in Literary Covers: A Case Study of Symbolic Expression in Lu Xun’s Call to Arms Cover - Xia Zhang,; Saiful Akram Che Cob,; Noor Azly Mohammed Ali,; Xuemin You,; Yujue Wang, (Wacana Seni Journal of Arts Discourse, 2025)
While symbolic metaphor is pivotal in conveying narratives and emotions in literary book covers, research on visual metaphors remains limited. This study addressed the gap by examining the cover of Lu Xun’s 1926 Call to Arms as a case study to explore how visual metaphors convey implicit meanings and authorial emotions within the book content. This analysis adopted Wilcox’s (2004) metonymic and metaphorical mapping model to analyse the symbolic elements on Lu Xun’s cover. The findings indicated that the cover layout represented the “iron house” restricting the national spirit; the typography “??” embodied the New Youth warriors calling for the national awakening from sleep through their literary works; the colour black signified the dark social reality, while the red conveyed both the pain of revolution, as well as the desire for a bright future. This paper also employed a conceptual integration network to blend the three metaphorical meanings to construct a cohesive interpretation, a visual manifesto of Lu Xun’s inner world for revolution. In summary, this study provides a practical analytical framework for interpreting the meanings of literary book covers, laying the groundwork for further studies.